PENINGKATAN LITERASI BANGSA BERBASIS KELEMBAGAAN MELALUI TAMAN BACAAN MASYARAKAT (TBM) - Nuryanto, Yayan; Rustandi, Encep; Raditiyanto, Satria (JURNAL KEBANGSAAN RI, 2025)
Abstract:. This article discusses how the Bandasari Village Government plays an active role in improving community literacy through strengthening the Community Reading Park (TBM) and the Development of Reading Corners spread across various strategic points in the village at the Al-Bayum reading park and Village Library. Using a descriptive qualitative approach, this study reveals the strategies, policies, and social impacts of literacy practices based on village institutions. The results of the study indicate that the commitment of the village government in forming the institutional structure of TBM, allocation of village funds, and synergy with external partners are strong foundations in building a culture of community literacy. This article recommends replication of the village government-based model as a national literacy strategy Keywords: community literacy, reading corner, institutions, government, village